Remote excitation and detection of surface-enhanced Raman scattering from graphene. Issue 22 (25th May 2018) - Coca-López, Nicolás; Hartmann, Nicolai F.; Mancabelli, Tobia; Kraus, Jürgen; Günther, Sebastian; Comin, Alberto; Hartschuh, Achim
Abstract : We demonstrate the remote excitation and detection of surface-enhanced Raman scattering (SERS) from graphene using a silver nanowire as a plasmonic waveguide. Abstract : We demonstrate the remote excitation and detection of surface-enhanced Raman scattering (SERS) from graphene using a silver nanowire as a plasmonic waveguide. By investigating a nanowire touching a graphene sheet at only one terminal, we first show the remote excitation of SERS from graphene by propagating surface plasmon polaritons (SPPs) launched by a focused laser over distances on the order of 10 μm. Remote detection of SERS is then demonstrated for the same nanowire by detecting light emission at the distal end of the nanowire that was launched by graphene Raman scattering and carried to the end of the nanowire by SPPs. We then show that the transfer of the excitation and Raman scattered light along the nanowire can also be visualized through spectrally selective back focal plane imaging. Back focal plane images detected upon focused laser excitation at one of the nanowire's tips reveal propagating surface plasmon polaritons at the laser energy and at the energies of the most prominent Raman bands of graphene. With this approach the identification of remote excitation and detection of SERS for nanowires completely covering the Raman scatterer is achieved, which is typically not possible by direct imaging.